The Impact of Advanced Practice Provider Staffing on Emergency Department Care: Productivity, Flow, Safety, and Experience. (31st July 2020) - Pines, Jesse M.; Zocchi, Mark S.; Ritsema, Tamara; Polansky, Maura; Bedolla, John; Venkat, Arvind; ,
Abstract: Objectives: We examined emergency department (ED) advanced practice provider (APP) productivity and how APP staffing impacted ED productivity, safety, flow, and experience. Methods: We used 2014 to 2018 data from a national emergency medicine group. The exposure was APP coverage: APP hours as a percentage of total clinician hours at the ED‐day level. Multivariable regression was used to assess the relationship between APP coverage and productivity outcomes (patients/clinician hour, relative value units [RVUs]/clinician hour, RVUs/visit, and RVUs/salary‐adjusted hour), flow outcomes (length of stay and left without treatment), safety (72‐hour returns, incident reports), and experience (Press‐Ganey scores), adjusting for patient and facility characteristics. Results: In 13.02 million patient visits in 105, 863 ED‐days across 94 EDs from 2014 to 2018, nurse practitioners and physician assistants managed 5.4 and 18.6% of visits independently, 74.6% by emergency physicians alone, and 1.4% jointly. APP visits had lower RVUs/visit (2.8 vs. 3.7) and lower patients/hour (1.1 vs. 2.2) compared to physician visits. Higher APP coverage (by 10%) at the ED‐day level was associated with lower patients/clinician hour by 0.12 (95% confidence interval [CI] = −0.15 to −0.10) and lower RVUs/clinician hour by 0.4 (95% CI = −0.5 to −0.3). There was no impact of increasing APP coverage on RVUs/salary‐adjusted hour or RVUs/visit. There was also no effect of increasing APP coverage on flow, safety, or patient experience. Conclusion: In this group, APPs treated less complex visits and half as many patients/hour compared to physicians. Higher APP coverage allowed physicians to treat higher‐acuity cases. We found no economies of scale for APP coverage, suggesting that increasing APP staffing may not lower staffing costs. However, there were also no adverse observed effects of APP coverage on ED flow, clinical safety, or patient experience, suggesting little risk of increased APP coverage on clinical care delivery.